Tax Law Perspective On Tax Collection On BPTHB Unpaid By Taxpayer In Medan - Satria, Frinan (AGUSPATI Research Institute, 2021)
Tax is the country’s biggest revenue source so that it plays a vital role in a country. Tax arrears in Indonesia are significant that they require law enforcement by fiscal authorities in collecting tax. The research problems are how the legal certainty is fulfilled in the provisions of collecting system of BPTHB (Duty on Land and Building Right Acquisition) in Medan, how the fiscal authorities and tax collecting for BPTHB that is underpaid by taxpayers. This study uses data sources consisting of: Primary legal materials are legal materials that have the highest level of legal force and become the main basis for analyzing this research. The legal materials can be in the form of the 1945 Constitution, the Law on General Provisions and Tax Procedures, the Law on Regional Taxes and Regional Levies, the Law on Collecting Taxes with Forced Letters, Government Regulation Number 91 of 2010.Secondary legal materials are materials that have a close relationship with primary legal materials, such as research results, seminar results, scientific papers, documents and books related to research. Tertiary legal materials are materials that provide primary legal information and secondary legal materials such as legal dictionaries, articles, magazines, tabloids, newspapers, and studies of all documents related to research.This is a prescriptive normative juridical research. It puts priority to primary legal materials such as the regulations related to tax laws.